(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2019)
Out of the four major skills, writing has become mandatory for academic success at secondary and tertiary levels. Writing has been taught for many years as a product rather than process during the students’ formative years. In fact, there are many writing activities prescribed at the secondary level. However, most of the writing activities are neglected in the pretext of paucity of time or due to lack of interest among some teachers who consider evaluating the written assignments and giving feedback as laborious and peripheral tasks. As teachers of writing we are prone to expose our students to the rules of writing and grammar without developing their ability to express their ideas. Having identified the challenges faced by engineering students during writing tasks, the present study used the ‘multiple draft strategy’ with relevant feedback as an experimental method to explore its significance in developing the writing skills of the students at the tertiary level.